2009 World Congress on Nature &Amp; Biologically Inspired Computing (NaBIC) 2009
DOI: 10.1109/nabic.2009.5395597
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent system for Arabic character recognition

Abstract: In this work, a new system for Arabic letter recognition is designed and implemented. New approaches for segmentation, processing, classification and hence recognition of characters and scripts are shown. The research concentrates on two important subjects: First, segmentation on the basis of word histogram and baseline estimation -a convenient algorithm is worked out for this aim. Second, the process of feature extraction to find the most useful points is implemented upon the given algorithm. Feature coding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In [3], found a popular defined size, skeletonization and thinning. The technique of thinning will convert the binary image of character into one pixel thick image used by [4]. Thresholding in this technique includes converting gray input images into document images of binary type for getting good features from the image [5], skew detection and correction [6], noise removal; the basic noise objective removal which is to eliminate all bit-patterns which are unwanted those did not have any value in the result.…”
Section: Preprocessingmentioning
confidence: 99%
See 2 more Smart Citations
“…In [3], found a popular defined size, skeletonization and thinning. The technique of thinning will convert the binary image of character into one pixel thick image used by [4]. Thresholding in this technique includes converting gray input images into document images of binary type for getting good features from the image [5], skew detection and correction [6], noise removal; the basic noise objective removal which is to eliminate all bit-patterns which are unwanted those did not have any value in the result.…”
Section: Preprocessingmentioning
confidence: 99%
“…In [23], used the longest spike which represented the baseline. In [4], used start-point also end-point of a character features and branch. Wavelet transforms features used by [32].…”
Section: Statistical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Feature extraction tackles the obstacle of cursiveness of Arabic in twofold: the global approach and the analytical approach. While global approach treats the word as a whole, extracts features from the unsegmented word, and then compares those features to a model [ 7 , 8 ], analytical approach decomposes the word into smaller units called glyphs [ 9 ]. Glyphs may or may not correspond to characters, although previous research has confirmed the difficulties in attempting to segment Arabic words into individual characters [ 10 ].…”
Section: Introductionmentioning
confidence: 99%